2021
DOI: 10.1097/mat.0000000000001643
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Transfusion and In-Hospital Mortality in Veno-Arterial Extracorporeal Membrane Oxygenation Patients

Abstract: Thrombocytopenia is common during extracorporeal membrane oxygenation (ECMO), and platelets are sometimes transfused to meet arbitrary goals. We performed a retrospective cohort study of veno-arterial (VA) ECMO patients from a single academic medical center and explored the relationship between platelet transfusion and in-hospital mortality using multivariable logistic regression. One hundred eighty-eight VA ECMO patients were included in the study. Ninety-one patients (48.4%) were transfused platelets during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…33 Further, there is growing evidence of the immunomodulatory and proinflammatory effects of donor platelets and their association with morbidity and mortality. 2,3,34 Similar to PRBC transfusions, observational studies have shown an association between higher volume of platelets transfused and mortality among pediatric ECLS patients. 13,35 A large multicenter point prevalence study showed that more than half of the plasma transfusions received by children on ECLS were prophylactic to prevent bleeding and not to treat ongoing hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Further, there is growing evidence of the immunomodulatory and proinflammatory effects of donor platelets and their association with morbidity and mortality. 2,3,34 Similar to PRBC transfusions, observational studies have shown an association between higher volume of platelets transfused and mortality among pediatric ECLS patients. 13,35 A large multicenter point prevalence study showed that more than half of the plasma transfusions received by children on ECLS were prophylactic to prevent bleeding and not to treat ongoing hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…33 Further, there is growing evidence of the immunomodulatory and proinflammatory effects of donor platelets and their association with morbidity and mortality. 2,3,34 Similar to PRBC transfusions, observational studies have shown an association between higher volume of platelets transfused and mortality among pediatric ECLS patients. 13,35…”
Section: Discussionmentioning
confidence: 99%
“…Studies of large databases have reported that children on ECMO receive platelet transfusions on 50–67% of all ECMO days; they receive a total median dose of 90 ml/kg of platelet transfusions during their ECMO run [34,35]. Similar to RBC transfusions, platelet transfusions to children and adults supported by ECMO have been independently associated with increased mortality, increased rate of thrombosis, and paradoxically, increased rates of bleeding [5 ▪▪ ,36,37]. Further studies are needed to prove causation and explore possible mechanisms.…”
Section: Transfusionsmentioning
confidence: 99%
“…12 Platelets were generally transfused to keep platelet count above 40 × 10 9 per liter in non-bleeding patients, above 50 × 10 9 per liter in patients with minor bleeding, and above 75 × 10 9 in patients with major bleeding. 13 Bleeding patients who had an international normalized ratio (INR) >1.5 had fresh frozen plasma (FFP) transfused, and those with fibrinogen <200 mg/dL had cryoprecipitate transfused. Platelet, INR, and fibrinogen targets were also subject to adjustment by the critical care team based on patients' clinical status.…”
Section: Anticoagulation Transfusion and Ecmo Practicesmentioning
confidence: 99%